FORMATION IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE NEEDS FOR REGULAR PHYSICAL CULTURE CLASSES (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of forming of students of higher educational establishments necessity in regular physical training; to produce the results of awn sociological research; to perform the principal motives of forming of students of necessity in regular physical training.
Keywords: necessities; students; physical training